(untitled) (Zien Journal of Social Sciences and Humanities, 2024)
According to the President of Uzbekistan Shavkat Mirziyoyev,a new approach and effective parliamentary control are important in the field of law-making. The role of the parliament in the system of political security and separation of powers is studied. Political security depends on the stability and efficiency of government institutions. The place and role of the parliament is recognized as a legislative body in many countries of the world. Formation of the government in the Republic of Uzbekistan and a number of reforms are being implemented in the process of parliamentary control. The article forms and functions of parliamentary control and analyzes its legal bases and divides the processes of parliamentarianism in the country into historical stages